2013
DOI: 10.3892/ol.2013.1712
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary plasmacytoma of the nasopharynx: A case report and review of the literature

Abstract: Plasmacytoma is an extremely rare and discrete solitary mass of neoplastic monoclonal plasma cells. Extramedullary plasmacytoma (EMP) tends to occur during the fifth and seventh decades of life and is rarely diagnosed in younger patients. Only four cases of EMP have been previously reported in relatively young patients. Here we report a 15-year-old patient presenting with long-term nasal obstruction, who was found to have EMP of the nasopharynx. The patient was treated with surgery followed by radiotherapy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 13 publications
(18 reference statements)
1
38
0
1
Order By: Relevance
“…Multiple myeloma is the most common type, bone solitary plasmacytoma, and soft tissue EMP being considerably less common (Table 4). 30 Genetic factors, smoking, chronic antigenic stimulation such as osteomyelitis, radiation exposure, and occupational exposures have also been reported as possible etiologic agents in the literature. 32 Wiltshaw et al 23 reported that 80% of extramedullary plasmacytomas occur in the head and neck region, and 40% of them occur in the nasal cavity and paranasal sinus, 20% in the nasopharynx, and 18% in the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple myeloma is the most common type, bone solitary plasmacytoma, and soft tissue EMP being considerably less common (Table 4). 30 Genetic factors, smoking, chronic antigenic stimulation such as osteomyelitis, radiation exposure, and occupational exposures have also been reported as possible etiologic agents in the literature. 32 Wiltshaw et al 23 reported that 80% of extramedullary plasmacytomas occur in the head and neck region, and 40% of them occur in the nasal cavity and paranasal sinus, 20% in the nasopharynx, and 18% in the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is generally recommended for recurrent, advanced, or disseminated disease. 30 Nasopharyngeal extramedullary plasmacytoma has a good prognosis but also requires a long-term follow-up to detect any local recurrence or progression towards multiple myeloma. Stage III has metastatic spread.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bone erosion may be present but can as well be caused by other neoplasms. Lymphadenopathy or disseminated disease is uncommon, but otherwise, the differentiation from nasopharyngeal lymphoma or carcinoma is generally not possible [3,4].…”
Section: Nasopharyngeal Lymphomamentioning
confidence: 99%
“…It comprises 5-10% of all plasma cell neoplasms. The most common sites of involvement are in the head and neck, particularly the upper respiratory tract (including the nasal cavity and the nasopharynx, which by itself is a rare occurrence) (1). To date, the origin of this type of tumor in chronic nasopharyngitis has not been described.…”
Section: Introductionmentioning
confidence: 99%